2017
DOI: 10.1037/bul0000111
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression as bidirectional risk factors for one another: A meta-analysis of longitudinal studies.

Abstract: Not only do anxiety and depression diagnoses tend to co-occur, but their symptoms are highly correlated. Although a plethora of research has examined longitudinal associations between anxiety and depression, these data have not yet been effectively synthesized. To address this need, the current study undertook a systematic review and meta-analysis of 66 studies involving 88,336 persons examining the prospective relationship between anxiety and depression at both symptom and disorder levels. Using mixed-effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
196
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 327 publications
(252 citation statements)
references
References 782 publications
17
196
2
8
Order By: Relevance
“…Importantly, depression or anxiety in adolescence is a strong predictor of these mental health disorders in adulthood. 4,12 …”
Section: Discussionmentioning
confidence: 99%
“…Importantly, depression or anxiety in adolescence is a strong predictor of these mental health disorders in adulthood. 4,12 …”
Section: Discussionmentioning
confidence: 99%
“…Approximately 67% of ED female inpatients have an anxiety disorder and 90% have depression (Blinder et al, ). Not only do anxiety and depression diagnoses tend to co‐occur, but their symptoms are highly correlated (Jacobson & Newman, ). Thus, there are several studies that have shown the presence of anxiety and depressive symptoms among ED patients (Brand‐Gothelf, Shani, Apter, & Fennig, ; Bühren et al, ; Godart et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most anxiety disorders have average ages of onset in childhood, with rates of anxiety-depression comorbidity substantially increasing during later adolescence and young adulthood (Merikangas et al, 2010;Wittchen, Kessler, Pfister, Höfler, & Lieb, 2000). Although the association between anxiety and depression is likely bidirectional (Jacobson & Newman, 2017), converging evidence suggests that for a substantial portion of comorbid youth, anxiety increases risk for depression under a likely "direct causation" model (Cummings, Caporino, & Kendall, 2014;Mathew, Pettit, Lewinsohn, Seeley, & Roberts, 2011). However, little is known about processes that may underlie this transition.…”
Section: Introductionmentioning
confidence: 99%